Anticancer therapeutic efficacy of biogenic Am-ZnO nanoparticles on 2D and 3D tumor models. (December 2021) - Chabattula, S.C.; Gupta, P.K.; Tripathi, S.K.; Gahtori, R.; Padhi, P.; Mahapatra, S.; Biswal, B.K.; Singh, S.K.; Dua, K.; Ruokolainen, J.; Mishra, Y.K.; Jha, N.K.; et al.
Abstract: The present study fabricates biogenic zinc oxide nanoparticles (ZnO NPs) with the aqueous leaf extract of Annona muricata ( Am ) plant collected from semi-evergreen forests of Odisha, India. The synthesized Am -ZnO NPs were physicochemically characterized. The ultraviolet/visible spectrum showed the maximum optical absorbance of Am -ZnO NPs at 355 nm. High-resolution transmission electron microscopy analysis presented the nearly spherical shape of Am -ZnO NPs with an average particle size of 80 nm. The net surface charge and hydrodynamic size of Am -ZnO NPs were measured to be ∼−2.59 mV and ∼417 nm, respectively. Am -ZnO NPs were found to be biocompatible and hemocompatible nature. Furthermore, Am -ZnO NPs displayed strong anticancer effects on both 2D and 3D tumor models. We observed a dose-dependent toxicity on both A549 and MOLT4 cells and observed a size reduction in the A549 tumor spheroids. Subsequently, we observed a depolarization in mitochondrial membrane potential of Am -ZnO NP–treated cancer cells leading to the apoptosis induction in cancer cells. Graphical abstract: Image 1 Highlights: Fabrication of Annona muricata -Zinc Oxide Nanoparticles ( Am -ZnO NPs) via green synthesis approach. Detailed physicochemically characterizations of Am -ZnO NPs. Strong anticancer activities of Am -ZnO NPs on both 2-dimensional (2D) and 3-dimensional (3D) tumor models. Am -ZnO NPs induced apoptosis with a depolarization in mitochondrial membrane potential (ΔΨm).